Enhancing Sensitivity to Audience Demands through Given-New Strategy - and Lugsamee Nuamthanom Kimura, Narat Kanprachar (Journal of Community Development Research (Humanities and Social Sciences); Vol 6 No 2 (2556): July - December 2013, 2014)
Writings produced by some L2 writers, especially novices, may be at times difficult to read, not only because of their author’s insufficient control of the English language, which results in global and local errors, but also because of the writer’s lack of understanding of audience demands, which affects the organization of information in their writings. Focusing on the latter problem, specifically by providing these writers with some linguistic tools corresponding to audience awareness, may help them approach their writings in a systematic way and subsequently enable them to effectively revise their own writings. This paper reviews the issue of audience in composition studies and demonstrates an application of a given-new strategy – a linguistic tool which constitutes cohesive ties, topic-comment analysis, and topical developments. This strategy can ultimately help L2 writers achieve higher quality writing through the organization of information that corresponds more closely to expectations of their general audience. Keywords: given-new strategy, L2 writing, audience, cohesion, topic-comment analysis
Keywords: given-new strategy, L2 writing, audience, cohesion, topic-comment analysis